2008
DOI: 10.1111/j.1475-6773.2007.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Quality Outcomes in Freestanding Ambulatory Surgery Centers and Hospital‐Based Outpatient Departments: 1997–2004

Abstract: There appear to be important variations in quality outcomes for certain procedures, which may be related to differences in organizational structure, processes, and strategies between ASCs and HOPDs. The study also confirms the importance of risk-adjustment for comorbidities when using administrative data, particularly for procedures that are sensitive to differences in severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 33 publications
4
37
1
Order By: Relevance
“…Even though mortality related to the ambulatory surgical setting is rare, this indicator has been used to flag potential quality problems associated with ambulatory surgery [6,7,9,25]. Other researchers have also used mortality as an outcome for comparing quality of care provided in the outpatient setting [8,12,26,27]. We used 7-day indicators since, as a shorter measure, it can reduce the effects of extraneous factors unrelated to outpatient procedures [6].…”
Section: Outcome Variablementioning
confidence: 99%
See 2 more Smart Citations
“…Even though mortality related to the ambulatory surgical setting is rare, this indicator has been used to flag potential quality problems associated with ambulatory surgery [6,7,9,25]. Other researchers have also used mortality as an outcome for comparing quality of care provided in the outpatient setting [8,12,26,27]. We used 7-day indicators since, as a shorter measure, it can reduce the effects of extraneous factors unrelated to outpatient procedures [6].…”
Section: Outcome Variablementioning
confidence: 99%
“…Due to the significant growth in the number of ambulatory surgical procedures provided in the U.S. and associated overall costs [4], researchers have begun to examine differences in quality outcomes for procedures performed in freestanding ambulatory surgical centers (ASCs) and hospital-based outpatient departments (HOPDs) [5][6][7][8][9][10][11][12][13][14][15]. Overall, these studies have utilized varying risk-adjustment approaches and have generally produced mixed results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young, unpublished data, 2010). 20,21,22,23 Finally, recent studies of RCs have found that they also engage in cream skimming the less severely ill patients but deliver less costly care, controlling for severity. 24,25 There is some evidence regarding quality standards practiced in such clinics and comparable levels of quality of care relative to physician offices.…”
Section: Radical and Disruptive Elements That Challenge Incumbentsmentioning
confidence: 99%
“…Previous research has compared the quality of care (Chukmaitov, Menachemi, Brown, Saunders, & Brooks, 2008) and financial performance (Chukmaitov, Tang, & Brooks, 2010) between ASCs and hospital-based outpatient departments. However, there is limited empirical work on market conditions that impact the proliferation of ASCs (Bian & Morrisey, 2006), the nature of competition between ASCs and general hospitals (Lynk & Longley, 2002), and the impact of the proliferation of ASCs on general hospitals.…”
mentioning
confidence: 99%